Protected Cultivation of High Value Vegetables and Cut Flowers A value chain approach - Hasan, M. (Indian Farming, 2015)
The export packaging technology for jasmine developed in the project has promoted jasmine export considerably. All possible efforts are being made to make the technology reach farther.